(untitled) (Research, Society and Development, 2022)
The Information and Communication Technologies (ICTs) are growing exponentially nowadays and consequently, it is a challenge for Brazilian education. In this context, the presente article is a bibliographic research that aimed to report how ICTs have been applied in public schools in Brazil, based on the hypothesis that the theme shows great achievements and also challenges to be overcome to improve education. For that, a bibliographic analysis was carried out in the technical and scientific publications on the SciELO, Google Scholar and CAPES’s Periodicals Portal as well as on renowned scientific journals in the field of education and technology. The analysis considered publications whose theme is the subject of this research. Overall, it was observed that the use of ICTs in education has as positive points: interactivity, greater engagement of students and the contextualization of school contents with the realities of each student and as negative points: lack of teacher training for better use of digital tools, lack of investment and infrastructure.